Possible anti-inflammatory, antioxidant, and neuroprotective effects of apigenin in the setting of mild traumatic brain injury: an investigation* - KOYUNCUOĞLU, TÜRKAN; YÜKSEL, MERAL; PEKER EYÜBOĞLU, İREM; AKAKIN, DİLEK (My University, 2022)
Objective Apigenin is a plant flavone proven with biological properties such as anti-inflammatory, antioxidant, and antimicrobial effects. This study, it was aimed to examine the possible anti-inflammatory, antioxidant, and neuroprotective effects of apigenin in the setting of the mild traumatic brain injury (TBI) model. Methods Wistar albino male rats were randomly assigned to groups: control (n = 9), TBI (n = 9), TBI + vehicle (n = 8), and TBI + apigenin (20 and 40 mg/kg, immediately after trauma; n = 6 and n = 7). TBI was performed by dropping a 300 g weight from a height of 1 m onto the skull under anesthesia. Neurological examination and tail suspension tests were applied before and 24 h after trauma, as well as Y-maze and object recognition tests, after that rats were decapitated. In brain tissue, luminol- and lucigenin-enhanced chemiluminescence levels and cytokine ELISA levels were measured. Histological damage was scored. Data were analyzed with one-way ANOVA. Results After TBI, luminol (p < .001) and lucigenin (p < .001) levels increased, and luminol and lucigenin levels decreased with apigenin treatments (p < .01-.001). The tail suspension test score increased with trauma (p < .01). According to the pre-traumatic values, the number of entrances to the arms (p < .01) in the Y-maze decreased after trauma (p < .01). In the object recognition test, discrimination (p < .05) and recognition indexes (p < .05) decreased with trauma. There was no significant difference among trauma apigenin groups in behavioral tests. Interleukin (IL)-10 levels, one of the anti-inflammatory cytokines, decreased with trauma (p < .05), and increased with 20 and 40 mg apigenin treatment (p < .001 and p < .01, respectively). The histological damage score in the cortex was decreased in the apigenin 20 mg treatment group significantly (p < .05), but the decrease observed in the apigenin 40 mg group was not significant. Conclusion The results of this study revealed that apigenin 20 and 40 mg treatment may have neuroprotective effects in mild TBI via decreasing the level of luminol and lucigenin and increasing the IL-10 levels. Additionally, apigenin 20 mg treatment ameliorated the trauma-induced cortical tissue damage.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; TOKSİKOLOJİ; IMMUNOLOGY; Life Sciences (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; TOXICOLOGY; Toksikoloji; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Genel İmmünoloji ve Mikrobiyoloji; Sağlık, Toksikoloji ve Mutajenez; Fizik Bilimleri; Pharmacy; Toxicology; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Immunology; General Immunology and Microbiology; Health, Toxicology and Mutagenesis; Physical Sciences; Apigenin; inflammation; oxidative stress; traumatic brain injury; neuroprotection; CEREBRAL ISCHEMIC-INJURY; NECROSIS-FACTOR-ALPHA; RAT-BRAIN; TNF-ALPHA; YGY-E; EXPRESSION; BARRIER; MODEL; INTERLEUKIN-1; IL-6